Ultraljudsundersökning av buken på vuxna nötkreatur - Broberg, Anna (SLU/Dept. of Clinical Sciences (until 231231), 2007)
Ultrasound is still a relatively new method for the diagnosis of abdominal conditions in cattle. The objective of this study is to evaluate ultrasound as a diagnostic tool for the common diseases affecting high-producing dairy cattle, for example traumatic reticuloperitonitis, right- and left displacement of the abomasum, fatty liver, wound infections and abscesses. This paper is a combined litterature study and a report of the results from ultrasound examinations of bovine patients at the ruminant clinic at the Swedish University of Agricultural Sciences. The study includes two healthy cows from the ruminant clinic, and seven patients with abdominal related diseases.